Pelatihan Penanganan Cardiac Arrest (Henti Jantung) dengan Menggunakan Metode Bantuan Hidup Dasar (BHD) Bagi Pengemudi Ojek Online Se Kota Medan - Siahaan, Dwi Lunarta D. S.; Sinatra, Jadeny; Nazma, Diani; Lubis, Andriamuri P.; Tanjung, Qodri F.; Sitepu, John Frans; Hamdi, Tasrif; Hamdani, Irfan; Chalil, M. Jalaluddin A.; Yunafri, Andri; Irina, Sinta; Zainumi, Cut M.; Fadinie, Wulan; Silaen, Ester L. R.; Simbolon, Boyke M.; Siahaan, Jekson M.; Lim, Hadyanto; Anto, Endy Juli; Tobing, Paul S. M. L.; Rimbun, Surjadi; Hutasoit, Eka Samuel P.; Tambunan, Ronald T. H.; Tarigan, Juliyanti; Stephanie S., Kezia; Natalie S., Karen (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
Cardiac Arrest is the leading cause of death in the world including Indonesia, which can occur anytime and anywhere. The causes vary, ranging from fatigue, and underlying health conditions, to traffic accidents. Basic Life Support (BLS) is the initial step that can be taken to restore respiratory and circulatory function in individuals experiencing respiratory or cardiac arrest. It is important for online motorcycle taxi drivers to possess these skills, as they often spend time on the road and interact with various people in different situations. Perhimpunan Dokter Spesialis Anesthesiology dan Terapi Intensif (PERDATIN) North Sumatra Branch concluded a series of Kursus Penyegar dan Penambah Ilmu Anestesia (KPPIA) by providing basic life support training to 521 public transport or online motorcycle taxi drivers in the city of Medan on September 29, 2024. Held at the Gedung Serba Guna of the North Sumatra Provincial Government, the participants were divided into 52 groups guided directly by anesthesiologist specialists as instructors. By providing this education and training, they can be better prepared to face emergency situations on the road, thereby enhancing safety and service for passengers